Practical Spectrophotometry: Exploring Maximum Absorption Peaks of Fe(SCN)₃ and CuSO₄ Solutions Using Visible Light - Riski Afandi (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study explores simple visible light spectroscopy to measure maximum absorption wavelengths in Fe(SCN)₃ and CuSO₄ solutions, analyzing the impact of light filters on absorption spectra. Methodology: This study exposed Fe(SCN)₃ and CuSO₄ solutions to tungsten lamp light, passing through a collimator and diffraction grating. Spectral data, recorded by a camera, compared filtered and unfiltered conditions. Absorbance, determined from light intensity differences, revealed characteristic wavelengths with maximum absorbance for each solution, visualized through wavelength-absorbance graphs. Main Findings: The maximum absorption wavelengths for Fe(SCN)₃ were 481 nm (with filter) and 472 nm (without filter), while for CuSO₄, they were 570 nm (with filter) and 553 nm (without filter). Monochromatic filters enhanced accuracy, aligning Fe(SCN)₃ closer to theoretical values and reducing CuSO₄ deviations to 20 nm (filtered) compared to 37 nm (unfiltered). Novelty/Originality of this study: The novelty of this study lies in the development of a simple visible light-based spectrophotometer by utilizing easily accessible tools and materials, such as tungsten lamps and CMOS cameras, to understand the maximum absorption peaks of Fe(SCN)₃ and CuSO₄ solutions. In addition, this study explores the effect of using light filters on the accuracy of spectrum data, providing a practical alternative for spectroscopy experiments in resource-limited learning environments.